Hubungan Penggunaan Smartphone Dengan Kualitas Tidur Pada Mahasiswa Keperawatan RS. Dustira - Hadiansyah, Tantan; Sarwendah, Endah (Jurnal Keperawatan Komplementer Holistic, 2023)
The group of people who undergo risky behavior in various forms of health problems, both physical and psychosocial, are teenagers. There needs to be attention to the health of adolescents because adolescents are an asset as well as an investment for future generations as well as potential human resources. Currently, the number of teenagers in Indonesia reaches approximately 20% of the population. This study aims to determine the relationship between smartphone use and sleep quality in students at the Hospital Nursing Academy. Dustira. The type of research used is the type of research in this research is descriptive correlative with a cross sectional approach. The population in this study is students and female students of the Hospital Nursing Academy. Dustira as many as 415 people. This sampling technique used Convaniece Sampling, which used the criteria of 381 teenagers. Data analysis used univariate analysis on each variable and then continued with bivariate analysis to see the relationship between the two variables using the chi-square analysis technique. Data collection was carried out using a questionnaire. The results showed that as many as 86% of respondents or the majority depended on smartphones. The general conclusion in this study is that there is a relationship between smartphone use and student sleep quality.